Collaborative Assessment Using QR-Code on Ethno-mathematics Learning for Pre-Service Teacher - Rahayu, Ratri; Ulya, Himmatul; ., Kartono; ., Isnarto; Kurniasih, Nuning (International Journal of Engineering and Technology, 2018)
This research is aimed to analyze the needs of collaborative assessment tools on ethno-mathematics learning. The subjects of this research are four lecturers of ethno-mathematics course, 87 college students in their 6th semester, and the head of Elementary Teacher Education study program of Faculty of Teacher Training and Education of Universitas Muria Kudus, Indonesia. The data is obtained from literary study and field surveys which includes documentation, questionnaire and interview. The technique used to analyze the data is data triangulation which consists of several steps, those are: reduction, data presentation, and conclusion based on the data description. The result of this research showed that (1) the students were not involved in making of ethno-mathematics learning assessment tools; (2) generally, the lecturers were lack in understanding that they did not applied the collaborative assessment on the ethno-mathematics learning; (3) assessment tools were needed to measure mathematical ability using QR-Code and studentsâ€™ disposition; (4) the lecturers expect that the guide book will provide the concept of collaborative assessment by using communicative language that detailed and practical so that it could be applied easily; (5) the guidebooks can accommodate lecturers' expectations.Â Â